Pengaruh Manajemen Laba, Leverage dan Intensitas Modal terhadap Agresivitas Pajak Perusahaan pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia - Ishak, Ishak; Akhmad Sadeli, Yudi; Ibrahim, Ibrahim; Charmelitha Mau, Lenny (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to determine and analyze the Influence of Earnings Management, Leverage, and Capital Intensity on Corporate Tax Aggressiveness in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the Period 2020 – 2023. By applying the Purposive Sampling method, this research takes the population of financial reports from 95 food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the Period 2020 – 2023. A total of 47 samples were selected for analysis in this study.